Michel Sittow Estonian painter at the courts of Renaissance Europe - Hand, John Oliver 1941-; Koppel, Greta 1978- (National Gallery of Art, 2017)
Michel Sittow (c. 1469-1525) was the greatest Estonian artist of the Renaissance. As his renown as a portraitist spread among the royal courts of Europe in the late fifteenth century, Sittow led the life of the itinerant artist, leaving his native Reval, the Hanseatic port city known today as Tallinn, to reside at courts in Spain, The Netherlands, and Denmark. Michel Sittow: Estonian Painter at the Courts of Renaissance Europe is the first monographic exhibit of this masterful artist's oeuvre. The 144-page catalog with 90 illustrations features rare paintings by Sittow and other art works by his contemporaries, along with insightful essays by leading European and American scholars including John Oliver Hand of the National Gallery of Art, Washington, and Greta Koppel of the Art Museum of Estonia, Tallinn....Provided by publisher